Bioinformatics Analysis of circRNA Expression and Construction of “circRNA-miRNA-mRNA” Competing Endogenous RNAs Networks in Bipolar Disorder Patients - HE, ling; Fu, Yonghui; He, Wenfeng; Zhou, Chaoxiong; Fu, xia; Wan, Qigen; Wei, Bo (Frontiers in Genetics, 2021)
Bipolar disorder (BD) is a severe mood disorder disease in China, and its underlying pathogenesis remains unknown. Circular RNAs (circRNAs) have been reported to play a key role in mental disorders and can be used as competitive endogenous RNAs (ceRNAs). However, little is known about the correlation of circRNAs with BD. In this study, Deep RNA sequencing was used to identify differentially expressed circRNAs (DE-circRNAs) and differentially expressed mRNAs (DE-mRNAs) between BD patients and a control group. Real-time quantitative reverse transcription-polymerase chain reaction (qRT-PCR) was used to validate the differentially expressed RNAs (DE-RNAs). In all 9,593 circRNAs and 20,030 mRNAs were found in the two groups of specimens, among which 50 DE-circRNAs and 244 DE-mRNAs were significantly upregulated, and 44 DE-circRNAs and 294 DE-mRNAs were significantly downregulated. Based on the regulatory mechanism of ceRNAs, circRNAs can directly bind microRNAs (miRNAs) to affect mRNA expression, and the expression trends of circRNAs and mRNAs are consistent. According to this mechanism, we constructed two ceRNA networks by using the RNA sequencing data. The function of these DE-circRNAs was further elucidated by enrichment analysis. In summary, the present study showed that the circRNA expression profile of BD patients is altered, and a ceRNA regulatory network was constructed, which provided a hypothesis about the pathogenesis of BD.